1999
DOI: 10.1002/(sici)1097-4644(19990915)74:4<499::aid-jcb1>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biological responses activated by nuclear protein kinase C

Abstract: Protein kinase C is a family of serine-threonine kinases that are physiologically activated by a number of lipid cofactors and are important transducers in many agonist-induced signaling cascades. To date, 12 different isozymes of this kinase have been identified and are believed to play distinct regulatory roles. Protein kinase C was thought to reside in the cytosol in an inactive conformation and translocate to the plasma membrane upon cell activation by different stimuli. Nevertheless, a growing body of evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 165 publications
0
35
1
1
Order By: Relevance
“…Studies from independent laboratories have led to the identification of quite few nuclear proteins which are PKC substrates and to the characterization of nuclear PKC-binding proteins which may be critical for fine-tuning PKC function in this cell microenvironment. Several lines of evidence suggest that nuclear PKC isozymes are involved in the regulation of biological processes as important as cell proliferation and differentiation, gene expression, neoplastic transformation, and apoptosis (interested readers should refer to [249, 254]). As mentioned above, certain PKCs also accumulate in mitochondria.…”
Section: Protein Kinase Cmentioning
confidence: 99%
“…Studies from independent laboratories have led to the identification of quite few nuclear proteins which are PKC substrates and to the characterization of nuclear PKC-binding proteins which may be critical for fine-tuning PKC function in this cell microenvironment. Several lines of evidence suggest that nuclear PKC isozymes are involved in the regulation of biological processes as important as cell proliferation and differentiation, gene expression, neoplastic transformation, and apoptosis (interested readers should refer to [249, 254]). As mentioned above, certain PKCs also accumulate in mitochondria.…”
Section: Protein Kinase Cmentioning
confidence: 99%
“…Almost all the isoforms of PKC have been identified at nuclear level, except for the PKCμ isoform [39,151]. The distinct functions of PKCs in the nucleus may be a consequence of either, the activity of resident isoforms of the enzyme or the translocation of PKC from cytoplasm to the nucleus, which may occur in certain conditions and in a different cellular system, as a result of nuclear lipid signaling [39].…”
Section: Pkc Phosphorylates Nox Subunits For Ros Generationmentioning
confidence: 99%
“…Moreover, nuclear PKCs have been implicated in cell proliferation, differentiation, apoptosis, and cardiovascular diseases [39,160]. For a complete review of nuclear PKCs and their function in cells see [39,151,161]. …”
Section: Pkc Phosphorylates Nox Subunits For Ros Generationmentioning
confidence: 99%
“…It has been reported that overall PKC activity in homogenates of LLC‐PK 1 cells decreased during confluence in parallel with activation of SGLT1 transcription, whereas in confluent LLC‐PK 1 cells phorbol ester‐mediated activation of PKC suppressed transcription of SGLT1 (19,31). These data suggest that phosphorylation of serine 370 in pRS1 is mediated by a specific PKC subtype that can be activated by phorbol esters (32,33) and/or that the regulation of SGLT1 transcription differs in subconfluent versus confluent cells. We investigated how inhibitors and activators of PKC influence nuclear location of the fusion proteins GFP‐pRS1 and βGal‐ (CK2‐RNS‐PKC‐PKC)‐GFP in subconfluent LLC‐PK 1 cells.…”
Section: Resultsmentioning
confidence: 80%